Pengaruh Shopping Life Style, Fashion Involvement, Hedonic Shopping Motivation Terhadap Impulse Buying Pada Masyarakat Kecamatan Sumbawa Pengguna Aplikasi Shopee - Serli Oktapiani; Hafizh Aldiansyah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to examine the effect of Shopping Life Style, Fashion Involvement, Hedonic Shopping Motivation on Impulse Buying in the Sumbawa District Society of Shopee Application Users. The sampling technique used is purposive sampling, which is the population used based on predetermined criteria to be used as samples. The study sample amounted to 100 people in Sumbawa District. The analytical tool used in this research is multiple linear regression. The results of this study indicate that Shopping Life Style has a positive and significant impact on Impulse Buying of the Sumbawa District Community, Shopee Application Users, Fashion Involvement has a positive and significant impact on Sumbawa District Community Impulse Buying, Shopee Application Users, Hedonic Shopping motivation has an influence on Impulse Buying Sub-district Community. Sumbawa Shopee Application User.